On The Flow and Fracture of Sea Ice: The Transition from an Anisotropic Continuum to a Granular Medium - Schulson, Erland M (2000)
The long-term goals are to understand the physical processes underlying the inelastic deformation of sheets of first-year sea ice, with the aim of improving sea ice models. The objectives are to understand the transition from continuum-like brittle compressive failure to granular-like sliding along sliplines/shear faults, and to formulate the sliding condition in terms of a physically-based failure criterion.